Quality Analysis Of Kue Ku With The Use Of Different Natural Dyes - Sari, Havivah Mayang; Faridah, Anni; Syarif, Wirnelis; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Kue Ku is a cake made from glutinous rice flour, coconut milk, sugar and salt with green bean filling in the shape of a turtle. Kue Ku which we often encounter in the market, is red in color which is attractive and even striking. In general, kue ku use synthetic dyes, but some traders use them with rhodamine B dyes. This study aims to analyze the quality of ku cakes using different natural dyes. The type of research used was a pure experiment, using a completely randomized design (CRD), with 3 repetitions. Data were analyzed using Analysis of Variance (ANAVA), if Fcount > Ftable then Duncan's Test was continued. The results showed that there was a significant influence on hedonic (liking). While shape, aroma, texture, taste did not show a significant effect. The overall best score is a neat and uniform shape of 4.33 (X1 and X3); fragrant aroma 4.00 (X1); chewy texture 4.00 (X1 and X3); sweetness 3.93 (X2 and X3); savory taste (X1, X2, and X3); and hedonic (liking) likes 3.80 (X3). The best result of this study was treatment (X3) using natural dyes from pumpkin.